LINC00518 Promotes Cell Proliferation by Regulating the Cell Cycle of Lung Adenocarcinoma Through miR-185-3p Targeting MECP2 - Han, Xu; Wu, Jixiang; Zhang, Yajun; Song, Jianxiang; Shi, Zhan; Chang, Huiwen (Frontiers in Oncology, 2021)
Previous studies have shown that long intergenic non-protein coding RNA 00518 (LINC00518) are essential for the cell growth and metastasis of human cancer. However, the role of LINC00518 in lung adenocarcinoma (LUAD) is still unknown. This research put emphasis on the function of LINC00518 on the cell growth of LUAD. The lncRNA, miRNA and mRNA expression were measured by using qRT-PCR. Protein levels were measured by using Western blotting. CCK-8, colony formation assays and transwell assay were performed to evaluate the cell proliferation ability and invasion. Bioinformatic analysis and luciferase reporter assays were chosen to confirm the mechanism of LINC00518 in LUAD. We found that LINC00518 was highly expressed in LUAD specimens and the high-expression was negatively correlated with the overall survival rates. This finding was also proved in the LUAD cell lines. Through a series of in vitro and in vivo experiments, we proved that LICN00518 promoted the cell growth of LUAD by regulating the cell cycle. Moreover, LICN00518 upregulated the expression of MECP2 by mutagenesis of miR-185-3p. The results suggested that LICN00518 could be used as a survival indicator and potential therapeutic target for LUAD patients.